2016
DOI: 10.1063/1.4951678
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap engineering of GaN nanowires

Abstract: Bandgap engineering has been a powerful technique for manipulating the electronic and optical properties of semiconductors. In this work, a systematic investigation of the electronic properties of [0001] GaN nanowires was carried out using the density functional based tight-binding method (DFTB). We studied the effects of geometric structure and uniaxial strain on the electronic properties of GaN nanowires with diameters ranging from 0.8 to 10 nm. Our results show that the band gap of GaN nanowires depends lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…It has been successfully used to calculate the electronic properties of bulk, surface, and nanowire systems [48,49], molecular materials [50], as well as some biological systems [51]. The success of DFTB to describe the electronic properties of many systems has been demonstrated through numerous comparisons with DFT, for example to calculate the structural and electronic properties of 2D phosphorous carbide polymorphs [52], or to study the effect of structural changes on the electronic properties of GaN nanowires [53]. Generally, DFTB agrees well with DFT and can therefore be utilized to study large-scale systems that are impossible to study with DFT.…”
Section: Methodsmentioning
confidence: 99%
“…It has been successfully used to calculate the electronic properties of bulk, surface, and nanowire systems [48,49], molecular materials [50], as well as some biological systems [51]. The success of DFTB to describe the electronic properties of many systems has been demonstrated through numerous comparisons with DFT, for example to calculate the structural and electronic properties of 2D phosphorous carbide polymorphs [52], or to study the effect of structural changes on the electronic properties of GaN nanowires [53]. Generally, DFTB agrees well with DFT and can therefore be utilized to study large-scale systems that are impossible to study with DFT.…”
Section: Methodsmentioning
confidence: 99%
“…The bandgap engineering has been a powerful technique for manipulating the electronic and optical properties of semiconductors. The electronic properties of GaN nanowires have been studied by Ming et al [96]. In that study, a systematic investigation of the electronic properties of GaN nanowires was carried out using the density functional based tight binding method (DFTB).…”
Section: Gan Nanowires Devicesmentioning
confidence: 99%
“…In that study, a systematic investigation of the electronic properties of GaN nanowires was carried out using the density functional based tight binding method (DFTB). The effect of geometric structure and uniaxial strain on the electronic properties of GaN nanowires with diameters ranging from 0.8 to 10 nm have also been studied [96]. The study's results showed that the band gap of GaN nanowires depends linearly on both the surface to volume ratio (S/V) and tensile strain.…”
Section: Gan Nanowires Devicesmentioning
confidence: 99%
See 2 more Smart Citations